PENGARUH PELAYANAN PURNA JUAL TERHADAP KEPUASAN PELANGGAN PADA PT SURYA TOTO INDONESIA TBK. - Dewi Victoria; Endang Ruswanti; Farichah . (Journal of Business & Banking, 2014)
PT Surya TOTO Indonesia Tbk, the Beauty-related industries such as home kitchen, the bathroomis a company in the field of sanitary and furniture which was established in 1977 inJakarta. This study aimed to test the depth of the effect of the delivery, installation, and warrantyclaims against TOTO customer satisfaction. This study was conducted in Jakarta onIndustry TOTO. The respondents are 124 customers who purchase the products of bathroomfixtures and kitchen with installation directly from the company of TOTO. It was conductedin mid-2013, and the data collection technique was using primary data processed by the applicationof SPSS version 20.0 for Windows. The analysis used linear regression analysis tomeasure how much the variable delivery, installation and warranty claims can affect customersatisfaction. The research hypothesis is found that there is a significant positive effectof delivery, installation and warranty claims TOTO products on customer satisfaction. Theresults of multiple linear regression analysis showed that there was also effect of the delivery,installation and warranty claims TOTO effect on customer satisfaction. Warranty claimsis the independent variable that is the most dominant influence on customer satisfaction.